A rare case of primary gastric tuberculosis presenting as gastric outlet obstruction mimicking malignancy - Singh, Kanika; Raychaudhuri, Sujata; Gole, Sheetal; Agarwal, Anu (International Journal of Scientific Reports, 2018)
Gastric tuberculosis (TB), both primary and secondary is a rare condition. It is less common in immunocompetent individuals and in those without any antecedent pulmonary infection. The nonspecific complaints like epigastric pain, vomiting and weight loss may be confounding and lead to difficulty in diagnosis and differential diagnosis may include adenocarcinoma. We present a case of an immunocompetent male who presented with the above mentioned symptoms and on endoscopy showed an ulcerated region in the pyloric antrum with gastric outlet obstruction. A differential diagnosis of adenocarcinoma was suggested by the clinician. The endoscopic biopsy revealed granulomas and giant cells with no evidence of dysplasia. However, Ziehl-Neelson stain for acid fast bacilli was negative. The diagnosis of gastric tuberculosis was confirmed on Polymerase chain reaction (PCR) test for TB. A possibility of gastric tuberculosis should always be kept in mind in an endemic country like India with nonspecific abdominal complaints like epigastric pain, weight loss, vomiting etc. along with other differential diagnosis. A correct clinicopathological diagnosis would help in the appropriate treatment of the patient and would prevent unnecessary surgical excision.